CTGF/VEGFA-activated Fibroblasts Promote Tumor Migration Through Micro-environmental Modulation - Wu, Wei; Zaal, Esther A; Berkers, Celia R; Lemeer, Simone; Heck, Albert J R (Molecular & cellular proteomics, 2018)
Fibroblast activation is associated with tumor progression and implicated in metastasis, but the initial triggering signals required to kick-start this process remain largely unknown. Because small cancerous lesions share limited physical contact with neighboring fibroblasts, we reasoned the first tumor-derived signal for fibroblast activation should be secreted and diffusible. By pulsed metabolic labeling and click-chemistry based affinity enrichment, we sieved through the ductal carcinoma secretome for potential fibroblast activators. Using immuno-depletion/supplementation assays on various secreted factors, we pinpointed that tumor-secreted CTGF/VEGFA alone is sufficient to activate paired mammary fibroblasts from the same patient via ROCK1 and JunB signaling. Fibroblasts activated in this manner are distinct in morphology, growth, and adopt a highly tumor-like secretion profile, which in turn promotes tumor migration by counteracting oxidative and lactate stress. These findings reveal a profound division-of-labor between normal and cancer cells under the directive of the latter, and allude to potential metastatic prevention through inhibiting local fibroblast activation.